Impact of titrating levels of dried distillers grains with solubles as a replacement of soybean meal on Boer goat fatty acid profiles - Rimmer, Linnea A.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Due to the rising goat population in the United States, there is growing economic incentive to feed dried distillers grains with solubles (DDGS) over soybean meal (SBM). However, there is limited knowledge of how it affects carcass composition. Therefore, the objective of this experiment was to evaluate the impact of titrating levels of DDGS as a replacement of SBM on Boer goat fatty acid profiles. Thirty-two Boer goat kids were fed isocaloric and isonitrogenous diets consisting of 0%, 33%, 66%, and 100% DDGS replacing SBM. There were no detected differences (P>0.05) in final body weight after a 47-d growth experiment. Goats were slaughtered in a commercial, USDA-inspected facility, backfat samples collected between the 12th and 13th rib, and samples analyzed for fatty acid profile via AOAC Official Method 996.06. Data were analyzed with goat as the experimental unit as a completely randomized design using the GLIMMIX procedure (SAS Institute Inc., v9.4, Cary, NC). Dietary treatment did not impact (P>0.05) the overall fatty acid profile or iodine value (50 to 52 points) of fat samples. This may be because fatty acids go through biohydrogenation by rumen bacteria, limiting the impact of diet on fatty acid profile. That said, increasing levels of DDGS impacted (P=0.03) both C16:1 and C18:3 in a quadratic manner. Specifically, goats fed 0% and 100% DDGS replacing SBM had higher C16:1 than those fed intermediate levels of DDGS, while the opposite was true for C18:3. No other fatty acid was affected (P>0.05), nor were there shifts in the ratio of saturated vs. unsaturated, or the total sum of n-3 fatty acids. In summary, fatty acid profiles are not significantly impacted by increasing levels of DDGS in place of SBM, and therefore DDGS can be used in Boer goat diets without impacting fat quality.
Keywords: Fall 2018